Interactive Mathematics Learning System (Smartmath) / Regina Tay Li Ling - Regina Tay , Regina Tay (2002)
Interactive Mathematics Learning System (Smartmath) is a Web-based Multimedia Learning-teaching system for lower primary school level. Primary school students, teachers, and parents are the target users of this system. It can be used as a teaching tool or as a self-learning program. The strength of Smartmath is that it provides lessons to educate users about basic mathematics operations according to users age group. Lessons are provided for children aged 7 and 8 which can also be used by preschool children. There are interactive quizzes that test the student's understanding after each lesson. Games based on mathematic operations and numbers are created for students to test their skills. This project aims to create an effective and interesting learning tool to enable students learn and enjoy mathematics at the same time. Smartmath, as a web-based application could promote and expose the use of computers to students at a tender age thus enhancing computer literacy. The waterfall model with prototyping will be development model used to develop Smartmath. The main advantage of this system is that the process can be tailored to meet the specific requirement yet possibly changing needs of any application. As Smartmath is an interactive multimedia web-based system, tools that will be used for the development of the system comprises of Macromedia Dreamweaver UltraDev and Adobe Photoshop. HTML, Javascript, and Java are the programming languages that will be used to develop the system. The main characteristics of this system are user-friendly, attractive interface, easy to navigate, interactive, and interesting with a talking wizard which serve as a guide.